Hardened body and method for producing the hardened body
By adding aluminum organic acid to the solidified body of steel smelting waste, aluminum hydroxylated glue is formed to inhibit the hydration reaction of free MgO, the problems of hydration expansion and insufficient strength are solved, and the high strength and crack resistance of the solidified body are achieved.
Patent Information
- Application Number
- JP2023077050
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-05-09
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-05-09
AI Technical Summary
The prior art is difficult to effectively suppress the hydration and expansion of free MgO in steel smelting waste, resulting in the expansion and cracks of the solidified body, and the strength of the solidified body is not sufficient to replace concrete.
Aluminum organic acid is added to the cured body containing free MgO, and the amount of aluminum organic acid is controlled during mixing, water filling and curing to form an aluminum hydroxylated glue to inhibit the hydration reaction of free MgO and at the same time to increase the strength of the cured body.
It effectively suppresses the hydration and expansion of free MgO, prevents the expansion of the solidified body from cracks, and increases the strength of the solidified body, so that it can replace concrete.
Smart Images

Figure 0007666541000001 
Figure 0007666541000002 
Figure 0007666541000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a hardened material capable of suppressing hydration expansion caused by free MgO, and a method for producing the same. [Background technology]
[0002] In the steelmaking process, MgO is sometimes added to the slag in excess of its saturation solubility to prevent the MgO contained in the refractory from dissolving in the slag during refining and damaging the refractory. The slag generated during this process contains MgO that did not react during refining and MgO that crystallized out when the slag was cooled. Such unreacted MgO and crystallized MgO are called free MgO.
[0003] Attempts to utilize steelmaking slag include hardened bodies using steelmaking slag, as disclosed in Patent Document 1, for example. However, slag containing free MgO has the property of expanding as the hydration reaction of the free MgO progresses over a long period of time, and there is a concern that the hardened body may expand and crack, making it difficult to use it as a raw material for the hardened body. Here, the hydration reaction of free MgO refers to a reaction in which the free MgO in steelmaking slag comes into contact with moisture such as rainwater or seawater to produce Mg(OH)2 (MgO+H2O→Mg(OH)2), and this reaction causes the volume to expand.
[0004] In the field of refractories, a method for inhibiting hydration of MgO by forming a crystalline coating of boric acid or the like on the surface of a refractory is well known, as disclosed in Patent Document 2. Patent Document 2 discloses a method for preventing smoldering of a basic refractory brick by forming a crystalline coating of one or more of sulfates, boric acid, and borates on the surface of the basic refractory brick, in which the basic refractory brick is impregnated with or coated with an aqueous solution having a value of 0.2 to 1.0 as expressed by the formula 100c / (a×b), where a(g) is the weight of water, b(g) is the saturation solubility, and c(g) is the weight of the solute, and then the aqueous solution is dried. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 10-152364 [Patent Document 2] Japanese Patent Application Publication No. 8-169783 Summary of the Invention [Problem to be solved by the invention]
[0006] However, based on the above-mentioned conventional technology, a slag hardened body containing B2O3 was experimentally produced using steelmaking slag containing free MgO as the material in order to suppress the hydration expansion of the free MgO. The 28-day compressive strength of the obtained hardened body was 20 N / mm 2 and was not suitable for use as a substitute for concrete.
[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a hardened body and a manufacturing method thereof that can suppress the volume expansion due to the hydration reaction of free MgO even when the hardened body contains free MgO and can solve the lack of strength of the hardened body. [Means for solving the problem]
[0008] The means for solving the above problems are as follows. [1] A slag containing free MgO, a binder, and an organic aluminum salt, the unit amount of the organic aluminum salt being 1.0 kg / m 3 More than 7.5kg / m 3 and the unit amount of the slag containing free MgO is 2650 kg / m 3 The following is a hardened body. [2] A method for producing a hardened body, comprising the steps of: mixing slag containing free MgO, a binder, and an organic aluminum salt to prepare a mixture; kneading the mixture by adding water; and hardening the kneaded mixture, wherein the unit amount of the organic aluminum salt mixed in the mixing step is 1.0 kg / m 3More than 7.5kg / m 3 and the unit amount of the slag containing free MgO is 2650 kg / m 3 The method for producing the cured body is as follows. Effect of the Invention
[0009] According to the present invention, even if the hardened body contains free MgO, the occurrence of expansion cracks caused by hydration expansion of the free MgO can be suppressed, and the hardened body has enough strength to replace concrete. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described below through the embodiments of the present invention. The hardened body according to the present embodiment is characterized in that an organic aluminum salt is used as the material. Although the details are not clear, it is considered that the following effects (1) to (3) can be obtained in the hardened body containing free MgO by using an organic aluminum salt.
[0011] (1) The organic acid in the organic acid aluminum salt forms a chelate on the surface of the free MgO, suppressing the hydration of the free MgO. (2) The aluminum ions in the organic aluminum salt form a gel-like aluminum hydroxide precipitate, which inhibits contact between the free MgO and water in the hardened body. (3) The aluminum hydroxide gel also acts as a binder, contributing to improving the strength of the hardened body.
[0012] Regarding (1) above, when organic aluminum salts are used, it is believed that the organic aluminum salts dissolve in the water in the hardened body and ionize to generate organic acid ions and aluminum hydroxide. On the surface of the free MgO, the lactic acid organic acid and Mg 2+ By forming a chelate with 2+ This stabilizes Mg 2+ +2H2O→Mg(OH)2+2H + The reaction is suppressed, and the production of Mg(OH)2 and the volume expansion associated with the production of Mg(OH)2 are suppressed.
[0013] Regarding (2) above, the gel-like aluminum hydroxide precipitate accumulates on the surface of the free MgO, preventing the free MgO from coming into contact with water. 2+ +2H2O→Mg(OH)2+2H + The reaction is suppressed, and the production of Mg(OH)2 and the volume expansion associated with the production of Mg(OH)2 are suppressed.
[0014] Furthermore, regarding (3) above, blast furnace slag powder and ordinary Portland cement are generally used as binders for hardened bodies, but it is thought that the gel-like precipitate of aluminum hydroxide generated from organic aluminum salts plays a role in supporting these binders. This makes the strength of the hardened body equal to or greater than that of hardened bodies that do not use organic aluminum salts. For the above reasons, it is necessary to use organic aluminum salts as a material for hardened bodies that contain free MgO in order to suppress the volume expansion caused by the hydration reaction of free MgO without reducing the strength of the hardened body.
[0015] In the hardened body according to this embodiment, the unit amount of organic aluminum salt contained in order to suppress the hydration expansion of free MgO is 1.0 kg / m 3 More than 7.5kg / m 3 Here, the unit amount of organic aluminum salt is 1 m of hardened body. 3 The organic acid aluminum content per unit.
[0016] The unit amount of organic aluminum salt is 1.0 kg / m 3 If the unit amount of organic acid aluminum is less than 7.5 kg / m, the effect of suppressing hydration expansion due to free MgO will be small. 3 If the amount is too large, the alkaline stimulation to the ground granulated blast furnace slag, which is the material for the hardened body, will be insufficient, and the hardened body will not solidify, resulting in a decrease in the strength of the solidified body.
[0017] The organic aluminum acid salt used in the hardened body according to this embodiment may be aluminum formate, aluminum citrate, aluminum oxalate, or aluminum lactate, and among these, it is preferable to use aluminum lactate. The organic aluminum acid salt may be any that dissolves in water. The organic aluminum acid salt may be not only a normal salt but also a basic salt. It is more preferable to use basic aluminum lactate as the organic aluminum acid salt. Furthermore, a solid organic aluminum acid salt may be used, or an aqueous solution of the organic aluminum acid dissolved in water may be used.
[0018] Ground granulated blast furnace slag may be used as the binder for the hardened body according to the present embodiment. Ground granulated blast furnace slag is obtained by pulverizing granulated blast furnace slag. Ground granulated blast furnace slag has a particle size of about 0.1 mm or less and a specific surface area of about 3000 cm2 measured by the Blaine method. 2 It is preferable to use ground granulated blast furnace slag having a molecular weight of 1 / g or more.
[0019] As the binder for the hardened body according to this embodiment, cement such as ordinary Portland cement, ecocement, fly ash, blast furnace cement, and early strength cement may be used in place of the ground granulated blast furnace slag, or in addition to the ground granulated blast furnace slag.
[0020] In addition, it is preferable to use slag containing free MgO as the aggregate of the hardened body according to this embodiment. As described above, even if slag containing free MgO is used, the occurrence of expansion cracks due to hydration expansion is suppressed by containing organic acid aluminum, and a hardened body having a strength that can replace concrete is obtained. This provides the effect of making effective use of slag containing free MgO, which cannot be used as a roadbed material or the like because it expands due to hydration.
[0021] The slag containing free MgO is a slag in which a periclase peak is confirmed by X-ray diffraction. As such a slag, it is preferable to use slag generated when melting a high-chromium molten iron alloy. Here, the high-chromium molten iron alloy refers to high-chromium molten steel (usually with a Cr content of 5% by mass or more) such as chromium-containing molten pig iron and stainless steel, and a chromium-containing mother molten metal for producing this high-chromium molten steel (for example, a molten iron alloy with a chromium concentration of 5% by mass or more and a carbon concentration of 1% by mass to 2% by mass, which is melted in an electric furnace, etc.).
[0022] Chromium-containing hot metal is usually produced by melting and reducing chromium ore in an electric furnace, an iron bath type smelting reduction furnace, or a shaft furnace type smelting reduction furnace. High chromium molten steel is produced through a primary refining furnace such as an electric furnace, a converter, or an AOD furnace, and a secondary refining furnace such as a VOD furnace, an RH degassing facility, or the like. The chromium-containing mother molten metal for producing high chromium molten steel is mainly produced in an electric furnace or a converter. Among these smelting furnaces, in a smelting reduction furnace for reducing chromium ore, an operation is performed in which MgO is added to the slag in an amount greater than the saturation solubility of the slag in order to protect the refractory of the furnace body, and the slag generated contains free MgO. It is preferable to use such slag containing free MgO as the aggregate of the hardened body according to the present embodiment.
[0023] The hardened body exhibits strength by filling gaps in aggregates such as slag with a paste consisting of ground granulated blast furnace slag, ordinary Portland cement, and water, and bonding them together. When slag containing free MgO is used as the aggregate in the hardened body according to this embodiment, the unit amount of the slag containing free MgO is 2650 kg / m 3 The unit amount of slag containing free MgO is preferably 2650 kg / m 3 If the unit amount of granulated blast furnace slag, ordinary Portland cement and water in the hardened body is too small, the adhesive strength of the aggregate is reduced, and the strength of the hardened body is reduced. 3 The content of each material contained in the product.
[0024] On the other hand, in the hardened body according to this embodiment, no lower limit is specified for the unit amount of slag containing free MgO. Slag containing free MgO functions as aggregate in the hardened body, but naturally, slag not containing free MgO or natural aggregate can also be used as materials. For this reason, it is not always necessary to use slag containing free MgO, so no lower limit is specified for the unit amount of slag containing free MgO. However, a small unit amount of slag does not promote effective use of slag containing free MgO, so the unit amount of slag containing free MgO is set to 100 kg / m 3 This has the effect of making effective use of slag containing free MgO, which cannot otherwise be used as roadbed material or the like due to hydration expansion.
[0025] In addition, the hardened body according to the present embodiment preferably further contains a high-performance water reducing agent. When the amount of water added during kneading is reduced in manufacturing the hardened body, the strength of the hardened body increases, but the material cannot be dispersed. In contrast, by adding a high-performance water reducing agent during kneading, the material can be dispersed while reducing the amount of water added, and the strength of the hardened body can be improved. As the high-performance water reducing agent, for example, Chupol, a polycarboxylic acid-based high-performance water reducing agent manufactured by Takemoto Oil Co., Ltd., can be used. In general, the amount of the high-performance water reducing agent used is preferably within a range of 0.3% by mass to 0.5% by mass of the total unit amount of the ground granulated blast furnace slag and ordinary Portland cement.
[0026] Next, a method for producing a hardened body according to this embodiment will be described. In the method for producing a hardened body according to this embodiment, first, slag containing free MgO as an aggregate, ground granulated blast furnace slag and cement as binders, and organic aluminum salt are mixed to form a mixture. This process is the mixing step. In this mixing step, the unit amount of organic aluminum salt to be mixed is set to 1.0 kg / m 3 More than 7.5kg / m 3 The following applies.
[0027] Next, water is added to the mixture and kneaded. This process is the kneading step. The kneaded mixture is cured for a predetermined period of time to harden, producing a hardened body. This process is the hardening step.
[0028] The above is a suitable method for producing a hardened body, but the method for producing a hardened body is not limited to the above method. For example, the mixing step in the above method for producing a hardened body may be omitted, and aggregate, binder, aluminum organic acid salt, and water may be mixed in a kneading step. In this way, aluminum organic acid salt and water may be added simultaneously in a kneading step rather than a mixing step, and kneaded. Also, a step of spraying an aqueous solution of aluminum organic acid salt onto aggregate may be provided before the mixing step, and the aggregate and aluminum organic acid salt may be mixed in the step, and the aggregate containing aluminum organic acid may be mixed with the binder in the subsequent mixing step to form a mixture.
[0029] As described above, the hardened body according to this embodiment has a hardness of 1.0 kg / m 3 More than 7.5kg / m 3 The following organic aluminum salts are contained. As a result, the hardened body according to this embodiment is able to suppress expansion cracks caused by hydration expansion even if the hardened body contains free MgO, and has the strength to replace concrete. EXAMPLES
[0030] Examples of the present invention will be described below. In these examples, a hardened body was manufactured using two types of slag (slag A and slag B) with the compositions shown in Table 1. In Table 1, "CaO / SiO2" indicates the ratio of the CaO concentration (mass%) to the SiO2 concentration (mass%) in the slag (hereinafter referred to as "basicity"), and "MgO" and "free MgO" indicate the MgO concentration (mass%) and free MgO concentration (mass%) in the slag, respectively.
[0031] [Table 1]
[0032] The slag shown in Table 1 was mixed with natural gravel (coarse aggregate), ground granulated blast furnace slag, water, basic aluminum lactate, and a high-performance water reducing agent in the proportions shown in Table 2 to produce a hardened body. In the inventive examples, basic aluminum lactate was used from among the organic aluminum salts, and the unit amounts of basic aluminum lactate were 1.0, 2.7, 5.2, and 7.5 kg / m 3 Basic aluminum lactate was prepared as a 25% by mass aqueous solution and added as part of the water to adjust the moisture content of the slag before kneading. In addition, a polycarboxylic acid-based water-reducing agent, Chupol manufactured by Takemoto Oil Co., Ltd., was used as a high-performance water-reducing agent.
[0033] Two types of hardened bodies were produced, one for strength measurement and one for expansion evaluation. The hardened bodies for strength measurement were removed from the form after hardening, and were cured underwater at 20°C until the age of 28 days, at which point the compressive strength was measured according to JIS A 1108:2018. The age of the hardened body is the number of days since it was cast.
[0034] The hardened specimens for expansion evaluation were removed from the frame after hardening and cured in water at 20°C for 14 days. After curing, they were immersed in water at 80°C. The hardened specimens were observed 45 days after immersion to check for the presence or absence of major cracks. The compressive strength was 20.0N / mm 2 The above was deemed to have passed. In addition, materials that had not solidified within 28 days and for which the compressive strength could not be measured were deemed "measurable." In addition, in the expansion judgment, materials that did not show any cracks in the hardened body were deemed to have passed, and materials that showed cracks in the hardened body were deemed to have failed.
[0035] The results of strength measurements and expansion evaluation of the hardened body using slag A are shown in Tables 2 and 3, and the results of strength measurements and expansion evaluation of the hardened body using slag B are shown in Tables 4 and 5. In Tables 2 and 4, ordinary Portland cement was used as the alkaline stimulant, and in Tables 3 and 5, ecocement was used as the alkaline stimulant.
[0036] [Table 2]
[0037] [Table 3]
[0038] [Table 4]
[0039] [Table 5]
[0040] As shown in Tables 2 to 5, the unit amount of basic aluminum lactate is 1.0 kg / m 3 More than 7.5kg / m 3 In all of the following invention examples, the 28-day compressive strength of the hardened body is 20.0 N / mm 2 The results showed that the material had sufficient strength to be used as a substitute for concrete. In addition, no significant cracks were observed even after immersion in 80°C water for 45 days, and the material passed the expansion test. These results confirmed that the expansion cracks caused by the hydration expansion of MgO were suppressed, and that the material had sufficient strength to replace concrete.
[0041] In Examples 49-52 and 110-113, the hardened bodies were manufactured using only ecocement as a binder, without using ground granulated blast furnace slag. In this way, the hardened bodies using only ecocement as a binder without using ground granulated blast furnace slag had a compressive strength of 20.0 N / mm2 after 28 days. 2 The results were also satisfactory, and the expansion test was also passed. These results confirmed that even when only ecocement was used as a binder, it was possible to suppress expansion cracks caused by the hydration expansion of MgO, and that the hardened body had the strength to replace concrete.
[0042] On the other hand, in Comparative Examples 1 to 6, 13 to 18, 25 to 30, and 37 to 42, in which basic aluminum lactate was not added, the 28-day compressive strength of the hardened body was sufficient, but large cracks were confirmed in the hardened body after immersion in water at 80°C for 45 days, and the expansion judgment was negative.3 In Comparative Examples 7 to 12, 19 to 24, 31 to 36, and 43 to 48, in which the hardened bodies were not solidified within 28 days of age, the compressive strength could not be measured.
[0043] Next, the results of strength measurements and expansion assessments of hardened bodies produced using hydrated lime instead of ordinary Portland cement or ecocement as a binder are shown in Tables 6 and 7 below.
[0044] [Table 6]
[0045] [Table 7]
[0046] As shown in Tables 6 and 7, the 28-day compressive strength was 20.0 N / mm2 even in the hardened body using hydrated lime as a binder, without using ordinary Portland cement or ecocement as a binder. 2 The results were also satisfactory, and the expansion test was also passed. These results confirmed that even when hydrated lime is used as a binder, rather than ordinary Portland cement or ecocement, it is possible to suppress expansion cracks caused by the hydration expansion of MgO, and to produce a hardened body with the strength to replace concrete.
[0047] Next, the results of measuring the strength and judging the expansion of a hardened body produced using slag B and aluminum phosphate, an inorganic salt of aluminum, instead of the organic aluminum salt, are shown in Table 8 below.
[0048] [Table 8]
[0049] In Comparative Examples 49 to 52, in which aluminum phosphate, an inorganic salt of aluminum, was added, the 28-day compressive strength of the hardened body was sufficient, but cracks were confirmed in the hardened body after 45 days of immersion in water at 80° C. For this reason, the expansion judgment for Comparative Examples 49 to 52 was negative, and no expansion suppression effect was obtained.
Claims
1. The present invention comprises a slag containing free MgO, a binder and basic aluminum lactate, The unit amount of the basic aluminum lactate is 1.0 kg / m 3 7.5kg / m or more 3 is as follows: The unit amount of the slag containing free MgO is 100 kg / m 3 or more and 2650 kg / m 3 is as follows: The binder is a hardened body in which the sum of unit amounts of ground granulated blast furnace slag and at least one of ordinary Portland cement, ecocement and slaked lime is 410 kg / m3 or more and 760 kg / m3 or less, the unit amount of the ground granulated blast furnace slag is 150 kg / m3 or more and 700 kg / m3 or less, and the unit amounts of the ordinary Portland cement, ecocement and slaked lime are 30 kg / m3 or more and 500 kg / m3 or less, or the binder is ecocement and its unit amount is 221 kg / m3.
2. A method for producing a cured body, comprising the steps of: mixing the slag containing free MgO, the binder and the basic aluminum lactate to form a mixture; A kneading step of adding water to the mixture and kneading it; A hardening step of hardening the kneaded mixture; having The unit amount of the basic aluminum lactate mixed in the mixing step is 1.0 kg / m 3 7.5kg / m or more 3 The unit amount of the slag containing free MgO is 100 kg / m 3 or more and 2650 kg / m 3 is as follows: A method for producing a hardened body, wherein the binder has a total unit amount of 410 kg / m3 or more and 760 kg / m3 or less of ground granulated blast furnace slag and at least one of ordinary Portland cement, ecocement and slaked lime, the unit amount of the ground granulated blast furnace slag being 150 kg / m3 or more and 700 kg / m3 or less, and the unit amounts of the ordinary Portland cement, ecocement and slaked lime being 30 kg / m3 or more and 500 kg / m3 or less, or the binder is ecocement and its unit amount is 221 kg / m3.
Citation Information
Patent Citations
Hardenable composition
JP1983145654A
Method for preventing slaking of basic firebrick
JP1996169783A
Hydration curing product utilizing steel-making slag
JP1998152364A
Production process of slag hardened body
JP2002308662A
Cement admixture, cement composition, and cement concrete composition using the same
JP2003221265A